The recovery and resilience facility: Key innovations and the interplay with cohesion policy - Francesco Corti; Matteo Pedralli; Chiara Pancotti (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
With the aim of contributing to the ongoing discussions on the future of post-2027 Cohesion Policy (CP), this chapter delves into the functioning of the Recovery and Resilience Facility (RRF). It examines the interplay between the RRF and CP, illustrating their respective governance structures, the key strengths of the RRF, the main obstacles to its implementation, and the interaction between the two instruments. The chapter concludes that the RRF can provide at least two sources of inspirration for the future of CP and EU public investment policies: the performance-based payment mechanism and the link between reforms and investments.
Keywords: 330; Performance-based budgeting; Recovery and Resilience Facility; Cohesion Policy; EU funding governance